The Influence of Platelet‐Like LaMgAl11O19 on the Toughness of 3 mol% Yttria Partially Stabilized Zirconia Ceramic. Issue 1 (18th September 2013) - Min, Xin; Huang, Zhaohui; Fang, Minghao; Liu, Yan'gai; Gao, Yuanfei; Liu, Fengjiao; Hu, Meiling; Tang, Chao; Qian, Tingting
<x xml:space="preserve">Abstract</x> LaMgAl11O19‐3 mol% yttria partially stabilized zirconia ceramics were successfully prepared by pressureless sintering at 1550°C for 3 h. The ceramic's mechanical properties were measured, and the phase composition and microstructure observed using X‐ray diffraction and scanning electron microscopy. The results show that the mechanical properties of the ceramic were initially improved on addition of LaMgAl11O19, but further additions were detrimental. When the amount of LMA added was equal to 2 wt.%, the bending strength and fracture toughness reached 812 ± 37 MPa and 14.0 ± 0.3 MPa·m1/2. This equates to an increase of 8.0% and 6.9% compared with untreated 3 mol% yttria partially stabilized zirconia (3YSZ) ceramic, respectively. However, the bending strength and fracture toughness both decreased when the amount of LaMgAl11O19 added was 4 and 6 wt.%. A crack propagation and force analysis of the crack tips in LaMgAl11O19‐platelet‐reinforced 3YSZ ceramic were also carried out. The results indicate that phase transformation and crack deflection were the dominant toughening mechanisms in the LaMgAl11O19‐3YSZ ceramic. At the same time, energy dissipation by the LaMgAl11O19 platelets also helps to restrain crack propagation in the matrix, which improves toughness more effectively.